Invention of a Ludic Tradition on a Croatian Island - Škrbić Alempijević, Nevena (2008)
In Bol on the island of Brač Carnival customs have been depicted by the inhabitants as a gathering point for all those feeling a bond with the place, and therefore play a significant role in the local community cohesion and self-identification. Their organizers have inscribed connotations of "authenticity" into them, thus defining them as a recognizable local brand. In the last decade the applicability of Carnival in promoting the place as a unique cultural destination has been perceived by local political decision-makers and tourism industry representatives. There was a need to transpose such ludic events from the winter period to already established summer celebrations, but also to invent new high-season events at which expressions of "the real Bol spirit" could be exhibited, in order to enrich the local cultural offer. Individuals most active in Carnival, considered to be the prominent carriers of local carnivalesqueness, have been invited by the local authorities and hotel managers to arrange playful performances at various summer occasions, such as: the fiesta (the celebration of the local patron saint's day), sports events (especially tennis tournaments), art exhibition openings, the closure of hotels, etc. Lay theatre performances, based on folk plays, socially critical jokes, derisive songs, disguises, bodily expressions and similar subversive motifs drawn from the Carnival context, have also been staged in Bol, oriented towards the tourist market. The transformation into transgressive figures, the actors' excessive usage of the body and their emphasized fictive sexuality characterize all these contemporary performances. Still, this performative stepping into what is otherwise considered socially unacceptable is not reflected in the public discourse. In the media and in tourist brochures the presentation of the local ludic tradition has taken a rather serious turn, since it has been placed on the pedestal of valuable local heritage.